Study of the effect of treatment with pomegranate peel extract on the microbial load of coated Awassi lambs’ meat samples when preserved by freezing - Al-Hamed, Raeed Ahmad; Al-Ali, Nuha Shehadeh; Abdel-Halim, Fateh Mamdouh; Al-Nasser, Mahmoud Hussein (Journal of agricultural, environmental and veterinary sciences, 2021)
In this study, the effect on the microorganism counts and the changes of this microbial load on the meat of Awassi lambs were studied after being packed and stored for 6 months under freezing conditions (-18 C) through treatment with pomegranate peel extract. The research tests were conducted in the laboratories of the Food Science Department at the Faculty of Agricultural Engineering in Deir Ezzor. The results of the microbial load counts showed significant differences in the numbers of intermediate thermophilic anaerobic bacteria between the samples treated with the extract and the control samples during the storage period. Significant differences were also observed in the numbers of E. coli bacteria, and the samples treated with concentration (1.5%) were the least numbered compared to samples treated with other concentrations. The average logarithm of the numbers of E. coli bacteria in the meat of Awassi lambs decreased from (7.74, 7.45, 6.64) in The beginning of the storage period to (3.72, 2.54, 1.21) at the end, when using pomegranate peel extract concentrations (0.5, 1, 1.5%) respectively. The average logarithm of the number of bacteria Pseudomonas according to the concentration of the extract (0.5%, 1%, 1.5%) from (11.07, 11.02, 10.46) at the beginning of the storage period to (7.12, 6.23, 2.98) at the end of the storage period, respectively, as for the control samples. (Other than the treatment with the extract), the number of bacteria increased in an insignificant way.